Finding a voice: Personal Statement Writing in the Age of Generative AI - Wilson, Sidney (My University, 2025)
This paper examines the impact of generative AI on the personal statement writing process for graduate school applications. Through a review of existing literature and interviews with both academic professionals and students, this paper explores AI’s role in drafting, editing, and reviewing personal statements. Drawing from the research articles, I aimed to investigate what is currently discussed in the field, including AI’s influence on the writing process, student perspectives on AI use, and the ability of admissions committees to detect AI generated writing. My interviews with academic professionals provided insights into the editing and reviewing stages of the application process, while interviews with students highlighted how AI shaped their writing process. This paper discusses the many advantages and disadvantages of AI’s use, as well as ethical concerns surrounding its current and future role in the admissions process. I also reflect on my own experience writing a personal statement for my optometry school application, tying together my initial thoughts on generative AI then discussing and applying what I’ve learned through this research. Ultimately, my findings suggest that if AI continues to expand rapidly into the graduate school application landscape, especially in the personal statement section, then clearer steps must be taken to ensure ethical use, proper education, and equitable access.